2016
DOI: 10.1038/ncomms11918
|View full text |Cite
|
Sign up to set email alerts
|

Operando NMR spectroscopic analysis of proton transfer in heterogeneous photocatalytic reactions

Abstract: Proton transfer (PT) processes in solid–liquid phases play central roles throughout chemistry, biology and materials science. Identification of PT routes deep into the realistic catalytic process is experimentally challenging, thus leaving a gap in our understanding. Here we demonstrate an approach using operando nuclear magnetic resonance (NMR) spectroscopy that allows to quantitatively describe the complex species dynamics of generated H2/HD gases and liquid intermediates in pmol resolution during photocatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 48 publications
(55 reference statements)
0
31
0
Order By: Relevance
“…6c ), indicating that the origin of H 2 is aqueous protons 82 . The presence of the H/D isotope effect decreases the photocatalytic HER 83 , but in principle, it does not harm our inferences about the source of H 2 in the reaction systems. To rule out the possibility that the protons were from hole scavengers (ascorbic acid, AA), the high-resolution mass spectra of the solution before and after the HER were applied.…”
Section: Resultsmentioning
confidence: 98%
“…6c ), indicating that the origin of H 2 is aqueous protons 82 . The presence of the H/D isotope effect decreases the photocatalytic HER 83 , but in principle, it does not harm our inferences about the source of H 2 in the reaction systems. To rule out the possibility that the protons were from hole scavengers (ascorbic acid, AA), the high-resolution mass spectra of the solution before and after the HER were applied.…”
Section: Resultsmentioning
confidence: 98%
“…For another, proton transfer and proton-assisted electron transfer play a key role in determining specific reaction pathways and photocatalytic efficiencies [9][10][11] , but there is no consensus on the mechanism of dynamic interfacial proton transfer. Previous studies have reported that molecularly adsorbed water or methanol can mediate the long-range proton transport on active photocatalytic surfaces [12][13][14][15] .…”
mentioning
confidence: 99%
“…Access to synchrotron techniques is still restricted, and the use of specialized equipment and purpose-built instrumentation is not universally accessible. Progress has been made toward developing lab-based in situ / operando approaches for the analysis of photocatalytic materials using, for instance, advanced laser techniques (Pastor et al, 2017 ) or in situ nuclear magnetic resonance (Wang et al, 2016 ). Even as core techniques applied ex situ , qualitative measures must be considered, since an inadequate analysis based on these techniques is still a source of frustration and controversy in the literature.…”
Section: Qualitative Approaches For the Assessment Of Photocatalytic mentioning
confidence: 99%